Rapid Hypertension Management with Acupuncture: Immediate Outcomes ofNeedling at Liver 3, Liver 2, Ear Shenmen, and Du 20. A Case Study. - Dharuman, Dr Annamalai; Murugan, Dr Narmatha; Vellingiri, Dr Madhumitha; Balu, Dr Abirami; Narasimhan, Dr Prabu; Sankar, Dr Geetanjali (Indian Journal of Integrative Medicine, 2025)
Hypertension (HTN) is a widespread global health issue and causes a major risk factor for cardiovascular diseases. It is often referred to as a “silent killer” because it is asymptomatic in its early stages. Obesity, dyslipidemia, age, smoking, and a sedentary lifestyle are all risk factors for hypertension, and the diagnosis of hypertension is based on office Blood Pressure measurement. While antihypertensive medications and lifestyle changes are recommended for managing high blood pressure, other therapies such as acupuncture are gaining attention, particularly in yoga and naturopathy settings. This case report presents a 43 year old male patient presented in the outpatient department with complaints of frequent headaches, excessive sweating, and difficulty in concentrating on his stressful work. His left hand office blood pressure readings were indicated to be 170/92 mmHg using a manual sphygmomanometer and 174/98 mmHg on a digital sphygmomanometer, indicating Stage 2 hypertension. Acupuncture with a sterile needle was administered at Liver 3, Liver 2, Ear Shenmen, and Du 20 points for 20 minutes as an immediate treatment. After the acupuncture session, the patient’s blood pressure was reduced to 144/84 mmHg (manual) and 147/88 mm Hg (digital). Additionally, the patient experienced relief from headaches. This case highlights the effectiveness of acupuncture for immediate reduction of blood pressure and symptomatic relief in hypertensive patients It adds value to managing hypertension in integrative healthcare settings such as yoga and naturopathy. However, while these results are promising, further research is needed to validate the effectiveness of acupuncture in broader populations and determine its benefits for acute hypertension management